Activation of the PPARγ Prevents Ferroptosis-Induced Neuronal Loss in Response to Intracerebral Hemorrhage Through Synergistic Actions With the Nrf2 - Duan, Chenyang; Jiao, Dian; Wang, Hanbin; Wu, Qiaoli; Men, Weidong; Yan, Hua; Li, Chunhui (Frontiers in Pharmacology, 2022)
Intracerebral hemorrhage (ICH) is a subtype of stroke characterized by high mortality and disability rates. The long-term effects of ICH-induced intracranial hematoma on patients' neurological function are unclear. Currently, an effective treatment that significantly reduces the rates of death and disability in patients with ICH is not available. Based on accumulating evidence, ferroptosis may be the leading factor contributing to the neurological impairment caused by ICH injury. Peroxisome proliferator-activated receptor γ (PPARγ) is a ligand-activated receptor in the nuclear hormone receptor family that synergistically interacts with the nuclear factor erythrocyte 2-related factor 2 (Nrf2) pathway to promote the expression of related genes and inhibit ferroptosis. Primary rat hippocampal neurons were treated with heme (50 μM) and erastin (50 μM) to induce ferroptosis, followed by the PPARγ agonist pioglitazone (PDZ, 10 μM) to verify the inhibitory effect of PPARγ activation on ferroptosis. ML385 (2 μM), a novel and specific NRF2 inhibitor, was administered to the inhibitor group, followed by an analysis of cellular activity and immunofluorescence staining. In vivo Assays, ICH rats injected with autologous striatum were treated with 30 mg/kg/d pioglitazone, and the inhibitor group was injected with ML385 (30μM). The results showed that PDZ inhibited ferroptosis in neurons by increasing the expression of PPARγ, Nrf2 and Gpx4 in vitro, while PDZ reduced ferroptosis in neurons after ICH and promoted the recovery of neural function in vivo. Our results suggest that PDZ, a PPARγ agonist, promotes Gpx4 expression through the interaction between PPARγ and the Nrf2 pathway, inhibits ferroptosis of neurons after ICH, and promotes the recovery of neural function.